Pengembangan Media Flashcard dengan Metode Peer Teaching Materi Pengaruh Kalor Terhadap Suhu dan Wujud Benda - Bahari, Priya Kusuma Bahari; Aynin Mashfufah; Hanafi, Yusuf; Salis Fariha Ramadhani; Anggraini, Ade Eka; Faizah, Siti (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
In the world of education, science learning is less effective if it is only done by rote memorization or passively listening to the teacher explain. In science learning activities, there must be a scientific process, producing scientific products by carrying out trials/experiments and forming students' scientific attitudes. The purpose of this research and development is to create Flashcard media by utilizing peer teaching strategies on material on the influence of heat on temperature and shape of objects, which is included in the valid category, which is approved by material experts, media experts, and teachers as users, and is practical and effective when used with science learning. The type of research used is Research and Development (R&D) with the ADDIE (Analyze, Design, Development, Implementation, and Evaluation) model. The research was carried out in trials at SDN 2 Plosokerep and testing at SDN 1 Kepanjenlor with subjects as fourth grade students. Data was obtained based on the results of observations, interviews, questionnaires and test evaluations. The Flashcard media validity test obtained an average score of 94.1% in the very valid category. The practicality test got an average of 89.1% in the very practical category and the effectiveness test with an average of 81% in the effective category. With the conclusion that this research and development can produce Flashcard media that meets the categories of validity, practicality and effectiveness tests.